A novel human-carrying quadruped walking robot. (18th July 2017) - Sang, Lingfeng; Wang, Hongbo; Yu, Hongnian; Vladareanu, Luige
This article adopts a 2-UPS+UP (U, P, and S are universal joint, the prismatic joint, and sphere joint, respectively) parallel mechanism as the leg mechanism of the quadruped walking robot based on the bionic concept and the motion capacity of the leg mechanism. The article investigates the kinematics (including the leg mechanism and the whole mechanism), gait planning, control, and experiment in detail. The following tasks are conducted: (1) designing the whole mechanism and developing the kinematics equations for both the leg mechanism and the whole mechanism; (2) planning the trotting gait and designing the foot trajectory based on the robot characteristics and conducting the kinematics analysis; (3) building the control system of the robot using self-developed controllers and drivers and studying the compound position control strategy; and (4) conducting the experiments for validating the controller, the compound position control strategy, the trotting pace, carrying capacity, and human-carrying walking. The results confirm that the proposed human-carrying walking robot has good performance and it is also verified that the controller and the compound position control strategy are suitable.